Implementation of Blended Learning System in Higher Education to Explore the Interaction of Technology, Organization, Environment, and Technology Acceptance Model - Hidayah, Nur Aeni; Aini, Qurrotul; Ghania, Putri (Bright Publisher, 2024)
A thorough examination of the deployment of blended learning after the COVID-19 pandemic is necessary to ensure its efficacy in enhancing the educational quality in higher education. The objective of this study is to identify the key elements that strongly impact the adoption of a blended learning system. It will be achieved by applying both the technology-organization-environment framework and the technology acceptance model. The study formulated eight hypotheses and administered online surveys on social media platforms to gather data from a total of 249 participants from four Islamic state universities. Analyzed data with the PLS methodology. The findings indicated that 92% of participants concurred that blended learning enhanced the quality of education. In addition, seven assumptions have been accepted, with the relationship between the technology context and the perceived ease of use in the blended learning system being the most relevant component. On the other hand, the PLS prediction results demonstrate that the suggested model possesses moderate predictive capability, as evidenced by its lower RMSE and MAE values in comparison to the linear regression model. Subsequent investigations should focus on analyzing the four blended learning models while taking into account factors such as teacher competence, educational systems, and social impacts.